Decision Support System for Determination Exemplary Employees Using Simple Additive Weighting Method (Case Study: BKN Office Yogyakarta) - Wahyu Widodo; Siswaya Siswaya; Sony Satya Nugraha (JEECS (Journal of Electrical Engineering and Computer Sciences), 2024)
The selection of exemplary employees is an annual event divided into three categories: civil servants, non-civil servants, and outsourced employees. Selection is based on four criteria: performance quality, discipline percentage, moral behavior, and leadership quality. The Assessment Team's assessment process for exemplary employees is carried out by recapitulating the assessment data for each work unit and determining exemplary employees from the recapitulation results using a manual form for evaluating employee performance within BKN Yogyakarta. Manual assessment requires quite a long time and has the risk of errors during the calculation process, so researchers see the need for a decision support system for selecting exemplary employees using the Simple Additive Weighting (SAW) method. This system helps the personnel department quickly and accurately rank exemplary employees. The system calculation results use the SAW method with 6 alternative employees with each score: Sudi 1, Heru 0.9, Vivid 0.82, Anjas 0.82, Tri 0.75, and Suwar 0.5. Sudi received the highest score and was designated as a model employee for this period.